Types and Abundance of Phytoperiphyton in the Plastic Substrate placed in the Putus Lake, SiakHulu Sub-District, Kampar District, Riau Province - Yuni Rahayu; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPhytoperiphyton is sessile microscopic organisms that attach on the substrates. A research aims to determine the type and abundance of phytoperiphyton on plastic substrate has been conducted on July-August 2019. There were three sampling stations, namely S1 (inlet area), S2 (middle of the lake), and S3 (the ends of lake). In each station, there were 2 sampling sites, in the surface (20 cm depth) and in the middle of water column (120 cm depth). The number of plastic substrates (8 x 3 cm2) in each station was 24 pieces.Samplingswere conducted once/week for a three weeks period. The phytoperiphytonwas sampledby brushing8 substrates/ sampling. Water quality parameters measured were temperature, transparency, depth, pH, dissolved oxygen, free carbon dioxide, nitrate and phosphate. Results shown that there were 29 types of phytoperiphyton and they were belonged to 4 classes, Bacillariophyceae (14 species), Chlorophyceae (11 species), Cyanophyceae (3 species) and Chrysophyceae (1 species). The abundance of phytoperiphyton in the plastic substrates placed in the S1 was 42,000 cells/cm2, in S2 was 29,285cells/cm2 and in S3 was34,195cells/cm2. The water quality parameters were as follows: temperature 29-300C, pH 5, transparency 64.1-71 cm, depth 2.46 – 3.33 m, dissolved oxygen 3.67– 4.90 mg/L, free carbon dioxide 3.45-8.11 mg/L, nitrate 0.026-0.047 mg/L and phosphate 0.035-0.058 mg/L.Water quality data indicate that the water of the PutusLakeis suitable to support the life of phytoperiphyton.Keywords : Oxbow Lake,Sessile Organism,Bacillariophyceae, Chrysophyceae